Новый вид паразитических перепончатокрылых рода Рагаschedius Mercet (Hymenoptera, Encyrtidae) из Восточного Крыма - Тряпицын, В.А. (Вестник зоологии, 1972)
Paraschedius caudatus sp. n. is described and key lo the females of the described species of the genus is given. The new species differs from P. ductor Merc. mainly in the presence ol two obscure anelli on hind tibiae and in protruding ovipositor. Besides, some Mediterranean elements of the Encyrtid fauna in the Crimea are listed in the ar-ticle.